RETRACTED: Changes in blood biochemical parameters during the implementation of adaptation processes in pigs under technological stress - Garskaya Natal`ya; Tresnitskiy Sergey; Garanovich Irina; Tresnitskiy Anatoliy (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001